South slavic comparative literary studies: contexts and course of development (Colloquia Comparativa Litterarum, 2025)
The article examines current trends in the development of South Slavic comparative literary studies. The discussion revolves around the reviewing of the notion of a South Slavic literary community and a unified South Slavic literary process. Interpretation focuses on the comparison of the Yugoslav and Post-Yugoslav literary contexts. Reference is made to the affiliation of South Slavic literatures to various cultural regions. The author comes to the conclusion that there is a need for a reviewing of South Slavic literatures as an open construction and a dynamic field of identities.
Keywords: South Slavic comparative literary studies; literary community; Yugoslav and Post-Yugoslav literary context; Southeastern European literatures.